The effect of petroleum hydrocarbons concentration on competition between oil-degrading bacteria and indigenous compost microorganisms in petroleum sludge bioremediation - Koolivand, Ali; Abtahi, Hamid; Parhamfar, Maryam; Saeedi, Reza; Coulon, Frederic; Kumar, Vinod; Villaseñor, José; Sartaj, Majid; Najarian, Niloofar; Shahsavari, Maedeh; Seyedmoradi, Paria; Rahimi, Leila; et al. (Elsevier, 2022)
The influence of the concentration of total petroleum hydrocarbons (TPHs) on competition between isolated oil-degrading bacteria (ODB) and finished compost microorganisms (FCM) was investigated in composting bioreactors over 12 weeks period. First, the batch tests were performed in Bushnell–Haas medium (BHM) to evaluate the biodegradation activities of six native ODB isolated from petroleum sludge (PS). Then, the ODB were added to the composting bioreactors containing 10 and 30 g/kg of TPHs. Based on the BHM results, the highest degradation efficiency of crude oil (1%–3% concentration) were determined to be 72%–75% at pH 7 after 7 days. In the composting bioreactors containing only the ODB, TPHs removal rates were 86%–92% after 12 weeks. Although the lower degradation efficiency of TPHs (73%–89%) in the bioreactors containing both the FCM and ODB indicated a slight competition between them, the ODB were still effective in the presence of the FCM especially at greater concentrations of TPHs. Despite the fact that the addition of finished compost (FC) to the PS changed the microbial composition in the composting bioreactors; the microbial populations exhibited little variation during the process. This study indicated that the isolated ODB, alone or in the presence of the FCM, effectively degraded the PS in the composting process.
Keywords: Bioremediation; Finished compost microorganisms; Oil-degrading bacteria; Petroleum sludge